The Molecular Signature of High-intensity Training in the Human Body - Wahl, Patrick; Bloch, Wilhelm; Proschinger, Sebastian (International Journal of Sports Medicine, 2021)
High-intensity training is becoming increasingly popular outside of elite sport for health prevention and rehabilitation. This expanded application of high-intensity training in different populations requires a deeper understanding of its molecular signature in the human body. Therefore, in this integrative review, cellular and systemic molecular responses to high-intensity training are described for skeletal muscle, cardiovascular system, and the immune system as major effectors and targets of health and performance. Different kinds of stimuli and resulting homeostatic perturbations (i. e., metabolic, mechanical, neuronal, and hormonal) are reflected, taking into account their role in the local and systemic deflection of molecular sensors and mediators, and their role in tissue and organ adaptations. In skeletal muscle, a high metabolic perturbation induced by high-intensity training is the major stimulus for skeletal muscle adaptation. In the cardio-vascular system, high-intensity training induces haemodynamic stress and deflection of the Ca 2+ handling as major stimuli for functional and structural adaptation of the heart and vessels. For the immune system haemodynamic stress, hormones, exosomes, and O2 availability are proposed stimuli that mediate their effects by alteration of different signalling processes leading to local and systemic (anti)inflammatory responses. Overall, high-intensity training shows specific molecular signatures that demonstrate its high potential to improve health and physical performance.
Keywords: haemodynamic stress; calcium signalling; metabolic stimuli; skeletal muscle; immune system; cardiovascular system